Directed biosynthesis of new saframycin derivatives with resting cells of Streptomyces lavendulae. - Arai, T (1985)
Saframycin A is an antitumor antibiotic produced by Streptomyces lavendulae 314 which falls into the category of the N-heterocyclic quinone group. Biosynthetically the quinone ring is derived from two tyrosine molecules which condense to generate the basic ring system of saframycin A. The side chain also has been found to derive from two amino acids, i.e., glycine and alanine. Supplementation by various amino acid analogs of the side chain produced three new saframycin derivatives with a replaced side chain. These three saframycins, designated Yd-1, Yd-2, and Y3, contained 2-amino-n-butyric acid, glycine, and alanine residues, respectively. in place of the normal N-terminal pyruvic acid in the side chain of saframycin A. Feeding experiments with 13C-labeled dipeptide indicated that the amino acids are probably incorporated in the side chain as a dipeptide unit. It was also found that saframycin A is produced from saframycin Y3 by an enzymatic deamination reaction. Based on these results, saframycin biosynthesis in S. lavendulae is discussed.